Selling Machinery to China: Chinese Perceptions of Strategies and Relationships - McGuinness, Norman; Campbell, Nigel; Leontiades, James (Journal of International Business Studies, 1991)
Chinese perceptions of machinery suppliers from six countries are used to evaluate supplier strategies and the customer relationships formed. Strategies based on product quality and service had the greatest impact on preferences. The relationship formed seemed to reflect mainly the perceived value of the product service-package offered. “Friendship” in the traditional Chinese sense did not seem to be a strong characteristic of these relationships.